Determination Of Optimal Tilt Angle For Solar Photovoltaic Panels In The Southern Regions Of Uzbekistan (Texas Journal of Engineering and Technology, 2026)
This article examines the trends in the development of solar energy in Uzbekistan, the solar energy potential, and the methodology for determining the optimal installation angles of solar panels. The optimal tilt angles of solar photovoltaic panels relative to the horizontal surface in Bukhara province were determined. The results showed that the average optimal tilt angle for summer months is 5° (≈ φ – 35°), while for winter months it reaches 65° (≈ φ + 25°). When using seasonally adjusted tilt angles are applied, the total annual collected solar energy amounts to 9252 MJ/m²·year. The annual average optimal tilt angle for south-facing solar panels was evaluated as 36°.